Analysis of Stress Asymmetric Distribution Law of Surrounding Rock of Roadway in Inclined Coal Seam: A Case Study of Shitanjing No. 2 Coal Seam - Xianyu Xiong; Jun Dai; Xinnian Chen (Advances in Civil Engineering)
Asymmetrical deformation and failure characteristics of the surrounding rock at the right-angled trapezoidal roadway in the Shitanjing No. 2 mining area has created great difficulties in the stability control and support of the roadway. First, numerical simulations were applied to systematically analyze the distribution rules for vertical stress, horizontal stress, and failure characteristics of the roadway. Furthermore, verifications were conducted via laboratory model tests and practical engineering application. The results show that the two walls of the roadway, the roof, and the sharp corners demonstrate obvious asymmetric stress concentrations. The peak value of stress concentration in the low side (right wall) is significantly greater than that in the high side (left wall), and the distances from high and low sides of roadway to both walls of the roadway are obviously different. The two sharp corners, which are symmetrical along the same direction of the coal seam inclination, show obvious compressive stresses, while the opposite directions show obvious tensile stress regions at both sharp corners; further, maximum values of the compressive and tensile stresses appear at the two corners of the roadway roof, and their magnitudes vary with the change in inclination and ground stress.